The great reset 100 days of Malaysia's triple crisis - Liew, Chin Tong (Research for Social Development, 2020)
There is talk that Perikatan Nasional is going to call a general election, banking on the hope that Malays will vote for a Malay government, and even deliver a two-thirds majority to Perikatan Nasional. Let me put it in simple terms, if I ever believe that only Chinese would vote for a Chinese party, I would not have joined the DAP in 1999; the year when Kit Siang and Karpal Singh both lost in constituencies with a high concentration of Chinese voters. Back in the early 2000s, we believed that Chinese and Indian voters would eventually vote for a multi-ethnic party, and that would be the DAP, and that with a multi-ethnic coalition, the Malays would come on board. Now, twenty years later, I still don't believe that Malays will vote for a Malay government simply because it is Malay in character, and without considering whether it is full of crooks or not. I believe many of my colleagues and comrades are in politics because we believe in the Malaysian Middle. We believe that there is a sizable middle group among Malay voters and among all ethnic groups who want to achieve clean government, smaller income gaps, and a country that we can all be proud of. It is our conviction that we can articulate a Malaysian civic nation or a new nationalism that every Malaysian can subscribe to and belong to. Malaysians who believe that the idea of Malaysia is one that is worth fighting for would have to rise to the occasion to lead the Great Reset for a better Malaysia.